Mode I fracture R-curve and cohesive law of CFRP composite adhesive joints. (April 2022) - Tauheed, Mohd.; Datla, Naresh V.
Abstract: This work presents the fracture R-curve behavior of composite adhesive joints with both brittle and ductile epoxy adhesives using double cantilever beam (DCB) specimens. Carbon fiber reinforced polymer (CFRP) laminates were bonded using a brittle adhesive (Araldite® AV138) and a ductile adhesive (Araldite®2015). The mode I fracture tests showed that the crack path for both adhesive joints was observed to be cohesive in the adhesive at crack initiation, while the crack path shifted to a mix of both cohesive and interfacial failure at the steady-state region. The fracture tests along with digital image correlation (DIC) of the crack tip images were used to extract a tri-linear traction-separation laws (TSL) for the ductile adhesive and a bi-linear TSL for the brittle adhesive joint. Finite element model of the DCB specimen developed using the TSLs reasonably predicted the experimentally measured load response of the joint. The stiffness degradation study of the cohesive elements showed that the extent of the damage ahead of the crack-tip is high for the ductile adhesive than for the brittle adhesive.